Bowens disease: clinico pathological correlation with review of literature - A., Rohini; Joseph, Leena Dennis; Priyadarshini, Anuradha (International Journal of Research in Dermatology, 2024)
Bowen’s disease is a type of squamous cell carcinoma in situ. It is most frequently diagnosed in the sixth to eighth decade of life. However, there have also been a few reports of pigmented Bowen’s disease. A single or multiple erythematous, round to irregular, scaly, keratotic, nodular, pigmented patches/plaques are first signs of the lesion. All cases of Bowen’s disease presented at a tertiary care centre over a period of seven years were included in this study. The patient details and clinical history were obtained from medical records. Histopathological slides of these cases were reviewed and analyzed. There were fourteen cases of Bowen’s disease with most patients belonging to 5-6th decade of life (80%). Males were more commonly affected (60%). Duration of the lesion ranged between 3-5 years in 60% of the patients. Most common site involved was lower back (80%). Most common presenting feature was hyperpigmented, erythematous plaques with scaling seen in 90% of the patients. Epidermal changes such as marked acanthosis with full thickness atypia were noted in 90 % and hyperkeratosis, parakeratosis was noted in 70% of the patients. Lichenoid infiltrates at dermo-epidermal junction was noted in 70% cases. The correct identification helps in appropriate diagnosis and treatment after biopsy confirmation. Adequate resection helps in preventing risk of invasive malignancy in these conditions.